2019
DOI: 10.1080/21645515.2019.1599673
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden and associated factors of measles patients in Zhejiang Province, China

Abstract: This study aimed to figure out the economic burden of measles patients and explore the associated factors for total cost in measles cases that occurred in the year 2015 from Jiaxing, Jinhua, and Taizhou cities in Zhejiang Province, China. Direct interviews were conducted to collect information on patient expenses during treatment, including outpatient expenses, hospitalization expenses, self-treatment fees, productivity loss, and transportation fees. Descriptive epidemiological methods and chi-square tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
4
0
3
Order By: Relevance
“…The influence of age on economic burden may be biased by vaccination. Previous studies [47][48] indicated that patients with insurance are likely to have clinical overtreatment and unnecessary use of expensive antiviral drugs, which is comparable to our study and leads to higher direct medical cost.…”
Section: Discussionsupporting
confidence: 85%
“…The influence of age on economic burden may be biased by vaccination. Previous studies [47][48] indicated that patients with insurance are likely to have clinical overtreatment and unnecessary use of expensive antiviral drugs, which is comparable to our study and leads to higher direct medical cost.…”
Section: Discussionsupporting
confidence: 85%
“…WHO guidelines for the elimination of measles suggest that large-scale outbreaks of measles can be avoided if the MCV coverage is more than 90% in the whole population and that at least 95% coverage could eliminate measles entirely ( 26 ). The Chinese government launched the National Expanded Program on Immunization (EPI) in 2007 that vaccinated with the MCV at 8 and 18 months of age ( 27 ). With these efforts, the measles incidence in China decreased dramatically, from 99.4 per million in 2008 when 151 cases were reported in the Zhoushan Islands ( Figure 1A ) to 4.6 in 2012 when two cases were reported in the Zhoushan Islands ( Figure 1A ) ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, with declining stockpiles (yellow fever), the discovery of gaps in immunity in young adults (rubella) [8] and a sharp recrudescence of cases (measles), strategies to sustain and improve the coverage of these existing vaccines are at the forefront, potentially delaying the introduction of vaccines against other diseases. To our knowledge, there is no other empirical cost-of-illness study for measles in lowincome settings: only a few were done in lower-and uppermiddle-income countries [9][10][11].…”
Section: Introductionmentioning
confidence: 99%